Systematics and phylogeny of Oecopetalum (Metteniusaceae), a genus of trees endemic to North and Central America - Hernández Urban, Humberto Adrian (2019)
The genus Oecopetalum Greenm. & C.H. Thomps. (Metteniusaceae) is distributed in the southeastern portion of Mexico to Central America (Guatemala, Nicaragua, and Costa Rica). Three species have been described and two have been reported as edible. We studied herbarium specimens of the genus Oecopetalum and performed a phylogenetic analysis based on the chloroplast genes matK and ndhF to answers to main questions: How many species are in the genus Oecopetalum? Is the genus Oecopetalum monophyletic? What are the generic relationships with other members of the family? Oecopetalum is a monophyletic genus with only two species. Pittosporosis is the sister group of Oecopetalum. The Trans-Atlantic relationship of Oecopetalum and Pittosporosis is a recurrent geographic pattern in the family Mettenuisaceae as well as in the family Icacinaceae. Our results, in concordance with fossil evidence and relationships of other groups, support the Boreotropical model of high-latitude terrestrial migrations of tropical taxa during the globally warm Paleocene–Eocene.